The Transcription Factor Runx2 Is under Circadian Control in the Suprachiasmatic Nucleus and Functions in the Control of Rhythmic Behavior - Reale, Meghan E.; Webb, Ian C.; Wang, Xu; Baltazar, Ricardo M.; Coolen, Lique M.; Lehman, Michael N. (PloS one, 2013)
Runx2, a member of the family of runt-related transcription factors, is rhythmically expressed in bone and may be involved in circadian rhythms in bone homeostasis and osteogenesis. Runx2 is also expressed in the brain, but its function is unknown. We tested the hypothesis that in the brain, Runx2 may interact with clock-controlled genes to regulate circadian rhythms in behavior. First, we demonstrated diurnal and circadian rhythms in the expression of Runx2 in the mouse brain. Expression of Runx2 mRNA and protein mirrored that of the core clock genes, Period1 and Period2, in the suprachiasmatic nucleus (SCN), the paraventricular nucleus and the olfactory bulb. The rhythm of Runx2 expression was eliminated in the SCN of Bmal1(-/-) mice. Moreover, by crossbreeding mPer2(Luc) mice with Runx2(+/-) mice and recording bioluminescence rhythms, a significant lengthening of the period of rhythms was detected in cultured SCN of Runx2(-/-) animals compared to either Runx2(+/-) or Runx2(+/+) mice. Behavioral analyses of Runx2 mutant mice revealed that Runx2(+/-) animals displayed a significantly lengthened free-running period of running wheel activity compared to Runx2(+/+) littermates. Taken together, these findings provide evidence for clock gene-mediated rhythmic expression of Runx2, and its functional role in regulating circadian period at the level of the SCN and behavior.